The cost of borders: Evidence from the Eurasian Customs Union - Hinnerk Gnutzmann; Arevik Gnutzmann-Mkrtchyan (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2020)
How strongly can the reduction in bureaucracy and red tape at the border increase trade? To address this, we study an ambitious trade facilitation policy - the complete abolition of internal customs controls - in the Eurasian Customs Union. Using a structural gravity model with high-dimensional fixed effects, we find evidence that non-tariff trade facilitation strongly and robustly increases the number of newly traded products. The value of trade, however, reacts more strongly to a traditional tariff-driven diversion of trade towards union members. Trade facilitation policies can diversify bilateral trade, highlighting the importance of trade analysis at the extensive margin.
Keywords: F14; F15; F55; 330; Außenhandel; Grenze; Handelsabkommen; Nichttarifäre Handelshemmnisse; Russland; Weißrussland; Kasachstan